THE UEFA EURO 2012 ANTI-DOPING PROGRAMME - SCIENTIFIC REVIEW - M. Earl; M. Vouillamoz; D. Kwiatkowska; E. Turek-Lepa; A. Pokrywka; M. Saugy; N. Baume; G. Gmeiner (Termedia Publishing House, 2014)
The final tournament of the UEFA European Football Championship is one of the top sporting events in the world, and a high-profile event of this kind requires a well-planned and well-executed anti-doping programme to ensure the integrity of results in the competition. UEFA EURO 2012 presented a unique logistical challenge, with the tournament spread across two countries, both covering a large geographical area. This paper discusses the planning and delivery of both the pre tournament out-of-competition (OOC) testing programme and the in-competition (IC) programme, as well as reviewing the activities of doping control officers (DCOs), the whereabouts programme and assessing the sample collection and transport process. The analytical approach applied is also discussed, along with an overview of the distribution of T/E ratios and blood parameters.